Influence of Talc Substitution with Starches from Different Botanical Origins on Rheological and Absorption Properties of Stiff Zinc Oxide Paste Formulations - Dragana Zaklan; Nikola Davidović; Jovana Milutinov; Dejan Ćirin; Veljko Krstonošić; Nebojša Pavlović (Pharmaceutics)
Background: Zinc oxide paste is traditionally compounded and applied in the therapy of various skin conditions. However, prolonged use of talc, usually present in zinc oxide pastes, may pose health risks due to potential contamination with asbestos and quartz, highlighting the need for alternative excipients. This study aimed to examine the effects of starches from various botanical sources and their particle size on the rheological and absorption properties of zinc oxide paste. Methods: Eight zinc oxide paste formulations were prepared, containing 25% zinc oxide and 25% indifferent excipient (talc, tapioca, rice, or maize starch) in two particle sizes. Rheological properties were assessed using amplitude and frequency sweep tests, and water- and oil-absorption capacities were determined using a centrifugation-based method. Results: Amplitude sweep tests confirmed the predominant solid-like nature of zinc oxide pastes, with the elastic modulus (G′) exceeding the viscous modulus (G″) in all formulations. Tapioca starch-based pastes exhibited the highest G′ and G″ values, while talc-based pastes exhibited the lowest. Frequency sweep tests showed that pastes were resistant to structural changes under stress, with G′ consistently dominating over G″ across the entire frequency range. Tapioca starch-based formulations exhibited the highest water-absorption capacity, while the talc-based formulations had the highest oil-absorption capacity. Reducing particle size improved both water- and oil-absorption capacities. Conclusions: Starches may be considered as alternatives to talc in zinc oxide pastes, due to their ability to modify the absorption and rheological properties of pastes. Future studies should assess the impact of starch substitution on sensory characteristics, shelf-life stability, and patient satisfaction.